The characteristics of positive ground discharges of tropical thunderstorms at Ibadan, Nigeria (2006)
Positive ground lightning discharges were continuously recorded over a period of three years at Ibadan to supplement earlier composite records from 1987 by adapting the earlier design of Oladiran. et al (1988a) using the shape of the radiation field signatures and the frequency components of positive discharges (Oladiran and Israelsson. 1990). We recorded 92% discrimination between negative and positive ground flashes. The positive ground flashes were recorded at VLF and 17.3kHz, 3Db attenuation and yielded an average 13 and 11.6% ratios for (+CG)/(-CG) respectively. Compared to our results of 1988, the flash-rate characteristics for positive ground flashes are not significantly different from those of negative ground flashes and it does not show any seasonal preference. This leads to the conclusion that the occurrence of positive and negative ground flashes depends only on the cloud charge structure. Its dynamics and the ground conditions.